Long-term care insurance and carers' labor supply: A structural model - Johannes Geyer; Thorben Korfhage (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In Germany, individuals in need of long-term care receive support through benefits of the long-term care insurance. A central goal of the insurance is to support informal care provided by family members. Care recipients can choose between benefits in kind (formal home care services) and benefits in cash. From a budgetary perspective family care is a cost-saving alternative to formal home care and to stationary nursing care. However, the opportunity costs resulting from reduced labor supply of the carer are often overlooked. We focus on the labor supply decision of family carers and the incentives set by the long-term care insurance. We estimate a structural model of labor supply and the choice of benefits of family carers. We find that benefits in kind have small positive effects on labor supply. Labor supply elasticities of cash benefits are larger and negative. If both types of benefits increase, negative labor supply effects are offset to a large extent.
Keywords: J22; H31; I13; 330; labor supply; long-term care; long-term care insurance; structural model